Association between overall dietary quality and constipation in American adults: a cross-sectional study - Qingye Liu; Yulong Kang; Jin Yan (BMC, 2022)
Abstract Background Constipation seriously affects people's life quality, and dietary adjustment has been one of the effective methods. Overall dietary quality has been reported to be associated with some diseases, while its association with constipation has not been reported. This study aims to explore the association between overall dietary quality and constipation. Methods A cross-sectional study was designed and data were extracted from National Health and Nutrition Examination Survey (NHANES). Overall dietary quality was assessed by healthy eating index-2015 (HEI-2015), and constipation was defined by either stool consistency or stool frequency. The association between overall dietary quality or components of HEI-2015 and constipation was assessed using logistic regression, with results expressed as odds ratio (OR) and 95% confidence intervals (95%CI). Subgroup analysis was conducted according to age and gender. Results A total of 13,945 participants were eligible, with 1,407 in constipation group and 12,538 in non-constipation group. Results showed that higher adherence to HEI-2015 was associated with reduced odds of constipation (OR: 0.98, 95%CI: 0.98-0.99) after adjusting potential confounders. Further, we found higher intake of total fruits, whole fruits, total vegetables, greens and beans, whole grains, total protein foods, seafood and plant proteins, and higher fatty acids ratio decreased the odds of constipation, while higher intake of sodium increased the odds (all P < 0.05). We also found negative association between HEI-2015 and constipation in participants with male sex, female sex, age ≥ 65 years, and age < 65 years (all P < 0.05). Conclusion We found higher adherence to HEI-2015 decreased the odds of constipation, suggesting that increasing HEI-2015 adherence may be one of effective methods to alleviate constipation.